2020
DOI: 10.1002/emp2.12158
|View full text |Cite
|
Sign up to set email alerts
|

Reducing aerosol dispersion by high flow therapy in COVID‐19: High resolution computational fluid dynamics simulations of particle behavior during high velocity nasal insufflation with a simple surgical mask

Abstract: Objective All respiratory care represents some risk of becoming an aerosol‐generating procedure (AGP) during COVID‐19 patient management. Personal protective equipment (PPE) and environmental control/engineering is advised. High velocity nasal insufflation (HVNI) and high flow nasal cannula (HFNC) deliver high flow oxygen (HFO) therapy, established as a competent means of supporting oxygenation for acute respiratory distress patients, including that precipitated by COVID‐19. Although unlikely to present a disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…HFNC use with a surgical mask placed over it may decrease the risk. [ 198 ] During all airway and respiratory maneuvers, extreme caution should be exercised, and the patient should be closely monitored for factors that would indicate a need for intubation, including decreasing or increasing respiratory rate, depressed mental status, worsening hypoxia despite escalating therapy, and inability to protect the airway. [ 190 ] During these advanced procedures, it is important to maintain the safety of HCWs by limiting the number of those directly caring for the patient to essential personnel and utilizing a negative pressure room (if available).…”
Section: S Ynopsis Of C Linical mentioning
confidence: 99%
“…HFNC use with a surgical mask placed over it may decrease the risk. [ 198 ] During all airway and respiratory maneuvers, extreme caution should be exercised, and the patient should be closely monitored for factors that would indicate a need for intubation, including decreasing or increasing respiratory rate, depressed mental status, worsening hypoxia despite escalating therapy, and inability to protect the airway. [ 190 ] During these advanced procedures, it is important to maintain the safety of HCWs by limiting the number of those directly caring for the patient to essential personnel and utilizing a negative pressure room (if available).…”
Section: S Ynopsis Of C Linical mentioning
confidence: 99%
“…Leonard et al 26 examined how the spread of COVID-19 can be mitigated through nasal inhalation with a surgical mask. The use of surgical masks has been recommended by numerous health care professionals to slow down the spread of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…The study was limited by the small population and questionable methodology, and further emphasized the current lack of systematic appraisal of airborne viral transmission from infected patients. Finally, an in silico computational fluid dynamics simulation by Leonard et al showed that using a simple surgical mask over the HFNC interface is effective in reducing distribution of aerosolized particles [13].…”
mentioning
confidence: 99%